Michael Cimino's Heaven's gate - Cimino, Michael 1939-2016; Carelli, Joann; Mansfield, David 1956-; Kristofferson, Kris 1936-2024; Walken, Christopher 1943-; Hurt, John 1894-1966; Waterston, Sam 1940- (The Criterion collection, 2012)
A Harvard graduate, turned federal Marshal in Wyoming, learns of a government sanctioned plot by cattle barons to kill the area's European settlers for their land. The resulting battle is based on the Johnson County War of 1892